Metodologia HALT no desenvolvimento de produtos em uma indústria de linha branca - Antunes, Chrys Marcell (Universidade Federal de São Carlos, 2025)
The white goods industry encompasses products such as refrigerators, freezers, and air conditioners, focusing on mature technologies with limited disruptive innovation. The demands of major white goods manufacturers led to the implementation of quality management systems, a reduction in the number of suppliers, and increased dependency between manufacturers and suppliers. The Highly Accelerated Life Testing (HALT) methodology is highlighted as essential for detecting early-stage issues in product development, ensuring greater reliability and quality, thus providing a competitive advantage by allowing the introduction of robust products to the market before competitors and reducing costs related to rework and recalls. This paper is a literature review, exploratory and descriptive in nature, aimed at emphasizing the importance of HALT in the product development process within the white goods industry. The main databases used were Google Scholar, Scopus, and ScienceDirect. The analysis involved a critical and systematic reading of the selected sources, and the synthesis of results was presented to highlight key trends and conclusions about the white goods industry, product development, reliability, and accelerated testing methodologies, including the application of HALT, to provide a comprehensive view of how this methodology contributes to product development and reliability in the white goods industry. It can be observed that the use of the methodology through a case study allowed the evaluation of the reliability of a component produced by a new supplier to validate whether it meets the product's life cycle based on consumer usage.
HALT methodology in product development in a white goods industry
Keywords: Xilitol; HALT - Highly Accelerated Life Testing; White goods industry; Product reliability and product development; Indústria de linha branca; Confiabilidade e desenvolvimento de produto; ENGENHARIAS::ENGENHARIA QUIMICA